Biodiesel Reactor Design with Glycerol Separation to Increase Biodiesel Production Yield - Rahmat, Budy; Setiasih, Imas Siti; Kastaman, Roni (Makara Journal of Technology, 2013)
The study consisted of reactor design used for transesterification process, effect of glycerol separation on transesterification reaction, determination of biodiesel quality, and mass balance analysis. The reactor was designed by integrating circulated pump/stirrer, static mixer, and sprayer that intensify the reaction in the outer tank reactor. The objective was to reduce the use of methanol in excess and to shorten the processing time. The results showed that the reactor that applied the glycerol separation was able to compensate for the decreased use of the reactant methanol from 6:1 to 5:1 molar ratio, and changed the mass balance in the product, including: (i) the increase of biodiesel production from 42.37% to 49.34%, and (ii) the reduction of methanol in excess from 42.37% to 32.89%. The results suggested that the efficiency of biodiesel production could be increased with the glycerol separation engineering.